2022
DOI: 10.3390/diagnostics12071687
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Diffusion Tensor Imaging for a Brachial Plexus Injury

Abstract: Brachial plexus injuries are commonly diagnosed clinically, as conventional imaging has a low sensitivity. In recent years, diffusion tensor imaging has established a clinical role in the study of the central nervous system and, while still presenting some limitations due to the technical complexity of the acquisition method, is showing promising results when applied to peripheral nerves. Moreover, deterministic fiber tracking with the Euler’s method and multishell acquisition are two novel advances in the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…DTI has been evaluated experimentally for imaging of the brachial plexus in animal models of nerve injury ( Chen et al, 2022 ) and in healthy volunteers ( Oudeman et al, 2018 ) and as a proof of concept for avulsion injuries ( Wader et al, 2020 ). Some authors report clinical use of diffusion images in their MRI protocol despite the artifacts ( Vara et al, 2022 ). Only one study reported use of DTI specifically for nTOS and reported abnormalities in 30% of patients of those who also had morphological changes in standard 3.0 T MRI exam.…”
Section: Discussionmentioning
confidence: 99%
“…DTI has been evaluated experimentally for imaging of the brachial plexus in animal models of nerve injury ( Chen et al, 2022 ) and in healthy volunteers ( Oudeman et al, 2018 ) and as a proof of concept for avulsion injuries ( Wader et al, 2020 ). Some authors report clinical use of diffusion images in their MRI protocol despite the artifacts ( Vara et al, 2022 ). Only one study reported use of DTI specifically for nTOS and reported abnormalities in 30% of patients of those who also had morphological changes in standard 3.0 T MRI exam.…”
Section: Discussionmentioning
confidence: 99%